2023
DOI: 10.3390/su15064997
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Well-Being Valuation for Sports, Culture and Leisure Activities

Abstract: It is widely acknowledged that engagement in sports, as well as in cultural and leisure activities benefits people’s well-being. However, what remains unclear is the monetary value of this contribution. For creating sustainable policies that withstand austerity measures, it is crucial to have a better understanding of the value of these activities. This scoping review provides the first overview of studies that estimate the value of leisure activities by using the compensating variation approach exclusively. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…These studies have used data from large-scale surveys and advanced statistical methods to explore the relationship between volunteering and SWB and assign a monetary value to this activity. The review of Schoemaker (26) identified two potential biases that can arise when using the wellbeing valuation approach. One important bias is the endogeneity of income, which refers to the possibility that unobserved factors may influence both income and wellbeing, leading to biased estimates of the effect of income on wellbeing.…”
Section: The Wellbeing Valuation Approach (Wva) For Volunteering In S...mentioning
confidence: 99%
“…These studies have used data from large-scale surveys and advanced statistical methods to explore the relationship between volunteering and SWB and assign a monetary value to this activity. The review of Schoemaker (26) identified two potential biases that can arise when using the wellbeing valuation approach. One important bias is the endogeneity of income, which refers to the possibility that unobserved factors may influence both income and wellbeing, leading to biased estimates of the effect of income on wellbeing.…”
Section: The Wellbeing Valuation Approach (Wva) For Volunteering In S...mentioning
confidence: 99%